Development of a simple method for simultaneous determination of tazarotene and betamethasone dipropionate and their metabolites using LC–MS method and its application to dermatopharmacokinetic study. (16th May 2019) - Li, Lingjun; Zhang, Mengli; Ma, Pengcheng; Qian, Kun
Abstract: In our study, a method for the determination for tazarotene and betamethasone dipropionate in human tissue‐engineered skin was established. Tazarotene gel, betamethasone dipropionate cream or a combination cream was administered to the skin. Then the skin was taken off at 0.25, 0.75, 1.75, 3, 5, 8, 12, 24, 36, 48 h time points after the residual drug was removed. The concentrations of tazarotene, betamethasone dipropionate and their major metabolites in skin were determined by LC–MS. Tazarotene and tazarotenic acid were detected in the concentration range of 2–200 μg/mL with an LLOQ of 2 μg/mL. Betamethasone dipropionate was detected in the concentration range 0.5–300 μg/mL with an LLOQ of 0.5 μg/mL, and betamethasone was detected at 2–200 μg/mL with an LLOQ of 2 μg/mL. The intra‐ and inter‐day precisions of the four analytes in the skin homogenate were all <15% (RSD, %). The results showed that tazarotene could be metabolized to tazarotenic acid and betamethasone dipropionate could be metabolized to betamethasone in tissue‐engineered skin. The results also revealed that this method was suitable for the simultaneous determination of tazarotene, betamethasone dipropionate and their metabolites in tissue‐engineered skin.